Challenges of Recruitment and Selection Process of Librarians in Federal University Libraries in South-South, Nigeria - Ufuoma, Eruvwe; Obiora Omekwu, Charles (International Journal of Knowledge Content Development & Technology, 2022)
The study investigated the challenges of recruitment and selection process of librarians in federal university libraries in South-South, Nigeria Two research questions were formulated to guide the study. The study adopted a descriptive survey. The population of the study consists of 108 librarians. 95 copies of the questionnaire were filled and returned. The questionnaire was used in collecting data. The overall reliability of the instrument yielded 0.95 with the use of Cronbach Alpha Coefficient. Standard deviation and mean was used to generate the data that was gathered. The rating scale of 4 points was subjected to an estimation procedure using SPSS version 17.0. A mean score of 2.5 and above on any item was accepted. The findings revealed that the librarians identified the challenges to include ethnicity influence; favoritisms; recruitment based on godfatherism; dwindling budgetary allocation. The librarians also indentified some of the strategies to include performance at interview as benchmark; equity and fairness as benchmark; recruitment should be done according to relevant discipline; and having channels for reporting cases of corruption during recruitment. Based on the findings, it was recommended as follows: Recruitment and selection of qualified librarians should be done according to the laid down procedures; and the library management should ensure that an independent judiciary and enforcement of the rule of law against culprits be adhered to, so as to ensure equity and fairness during recruitment and selection of librarians.